Does Using Korean Brand Ambassadors Affect Purchase Intention? - Choiriyah, Patin; Puspita, Rosana Eri (Jeksyah: Islamic Economics Journal, 2024)
This study aims to determine how strong the influence of brand awareness, marketing strategy, halal label, and price on purchase intention of Scarlett whitening x exo body lotion products in salatiga Muslim communities with religiosity as a moderating variable. This study used quantitative methods by taking primary data and distributing questionnaires to 100 respondents using purposive sampling techniques. Based on the tests: 1) Brand awareness has no positive and insignificant effect on purchase intention. 2) marketing strategy has a positive and significant effect on purchase intention. 3) Halal labels have a positive and significant effect on purchase intention. 4) price has a positive and insignificant effect on purchase intention. 5) religiosity moderates the relationship between the influence of brand awareness and purchase intention. 6) religiosity moderates the relationship between the influence of marketing strategy and purchase intention. 7) religiosity moderates the relationship between the influence of halal labeling on purchase intention. 8) religiosity moderates the relationship between the effect of price and purchase intention.